Tourist Experience and Technology-Enhanced Activities: The Mediating Role of Halal Value Perception on Revisit Intention in Samosir (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
Tourism in culturally hybrid destinations requires the integration of authentic experiences, technology adoption, and religious values to foster sustainable competitiveness. This study investigates how tourist experience quality and technology-enhanced tourism activities influence revisit intention through the mediating role of perceived halal value in Samosir, North Sumatera. A quantitative survey was conducted with 300 Muslim visitors, and data were analyzed using partial least squares structural equation Modeling (PLS-SEM). The results revealed that both tourist experience quality and technology-enhanced tourism activities significantly improved perceived halal value, which, in turn, strongly predicted revisit intention. Technology-enhanced activities exerted the strongest direct and indirect influences, confirming their role as a dominant driver of halal value creation. Mediation tests showed that perceived halal value significantly strengthened the pathways from both antecedents to revisit intentions. The model explained 67.8% of the variance in perceived halal value and 63.1% of the variance in revisit intention, indicating its substantial explanatory power. This study was limited by its focus on a single destination and its cross-sectional design, which may constrain generalizability and causal inference. Despite these limitations, the findings contribute to halal tourism literature by demonstrating the critical role of technology in reinforcing value perception and loyalty in emerging Muslim-friendly destinations. Practically, this study highlights the need for destination managers to integrate authentic cultural experiences with smart halal-compliant technologies to enhance tourist trust, satisfaction, and long-term commitment.Practically, the study provides actionable insights for destination managers and policymakers to integrate smart, halal-compliant technologies with authentic cultural experiences, thereby strengthening tourist trust, satisfaction, and sustainable competitiveness in halal tourism markets.